Association Between Sources of Social Support and Depression Among Nursing Students During the COVID-19 Pandemic - Dedi Kurniawan; Akbar Satria Fitriawan; Wiwit Ananda Wahyu Setyaningsih; Apri Nur Wulandari; Eriyono Budi Wijoyo; Erni Samutri; Gatot Suparmanto; Bayu Fandhi Achmad; Listyana Natalia Retnaningsih; Putri Eka Sudiarti (Nurse Media: Journal of Nursing)
Background: Nursing students have a higher risk of depression due to their high academic burden, social isolation, pandemic loneliness, abrupt online learning, and financial difficulties during the COVID-19 pandemic lockdown. Although the disruption of social network patterns during the pandemic has been observed in previous studies, it is still not fully understood which source of social support is associated with depression among nursing students.